2013
DOI: 10.1051/0004-6361/201321541
|View full text |Cite
|
Sign up to set email alerts
|

Rapid cooling of Cassiopeia A as a phase transition in dense QCD

Abstract: We present a model of the compact star in Cassiopea A that accounts for its unusually fast cooling behavior. This feature is interpreted as an enhancement in the neutrino emission triggered by a transition from a fully gapped, two-flavor, color-superconducting phase to a crystalline phase or an alternative gapless, color-superconducting phase. By fine-tuning a single parameter -the temperature of this transition -a specific cooling scenario can be selected that fits the Cas A data. Such a scenario requires a m… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
56
1

Year Published

2015
2015
2018
2018

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 60 publications
(59 citation statements)
references
References 40 publications
(64 reference statements)
2
56
1
Order By: Relevance
“…In this Section we summarize the results of the studies of cooling of hybrid compact stars carried out in Refs. [12][13][14]. As part of this program, the rapid cooling of the compact star in Cassiopea A (hereafter Cas A) was modelled as a phase transition within the QCD phase diagram [13].…”
Section: Cooling Of Compact Starsmentioning
confidence: 99%
See 1 more Smart Citation
“…In this Section we summarize the results of the studies of cooling of hybrid compact stars carried out in Refs. [12][13][14]. As part of this program, the rapid cooling of the compact star in Cassiopea A (hereafter Cas A) was modelled as a phase transition within the QCD phase diagram [13].…”
Section: Cooling Of Compact Starsmentioning
confidence: 99%
“…[12][13][14]. As part of this program, the rapid cooling of the compact star in Cassiopea A (hereafter Cas A) was modelled as a phase transition within the QCD phase diagram [13]. The latest updated data [15] that covers the 10 year period from 2003 to 2013 was fitted in Ref.…”
Section: Cooling Of Compact Starsmentioning
confidence: 99%
“…Refs. [65,56] demonstrated that Cas A data could be explained within the hybrid star scenario exploiting stiff hadronic EoS.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, recent discovery with the aid of the NASA's Chandra X-Ray Observatory of unusually fast cooling of supernova remnant in Cassiopeia A (Cas A), which is the youngest known neutron star (NS) in the Milky Way Galaxy, has attracted great attention (see, e.g., [16][17][18][19][20][21][22][23][24][25][26][27][28][29][30] and references therein). Several authors [18][19][20][21][22][23] explain such rapid cooling of NS in Cas A during last years (since August 1999, when Chandra found point x-ray source in the Cas A, up to 2014) due to the existence of spin-triplet superfluidity of neutrons inside high-density liquid outer core of this NS.…”
Section: Introductionmentioning
confidence: 99%
“…Several authors [18][19][20][21][22][23] explain such rapid cooling of NS in Cas A during last years (since August 1999, when Chandra found point x-ray source in the Cas A, up to 2014) due to the existence of spin-triplet superfluidity of neutrons inside high-density liquid outer core of this NS. But alternative explanations for the observed rapid cooling of Cas A have also been proposed (see, e.g., [24][25][26][27][28][29] and the discussion of [24] in [20,21]). This NS in Cas A is the first one whose cooling has been observed in the real time.…”
Section: Introductionmentioning
confidence: 99%